TRADITIONAL VALUES IN THE ERA OF TECHNOLOGY AND INNOVATION - Läänemets, Urve; Kalamees-Ruubel, Katrin; Sepp, Anu; Kiilu, Kristi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Several factors, such as international trends of globalisation, technological innovation, changing learning environments as well as internal developments in socio-cultural contexts and educational policy-making are constantly shaping values of people and causing difficulties with specification of their identity building. Our study is based on comparative research carried out in Estonia and Finland in 2015-2018 (N = 217) with future music teachers, who were asked to write essays where they highlighted and explained meaningful for them cultural landmarks in their countries. The method used was hermeneutical analysis, as this allows to focus on the text produced according to the question asked as an expression of the respondents’ personal experiences and accepted values. The information presented in texts was analyzed at multiple levels and different viewpoints. Parallel analyses by authors were carried out in order to guarantee the validity of the overall results. Finally, the results were grouped, which allowed to draw preliminary conclusions what the common cultural landmarks were and why they have been accepted and recognised as meaningful and valuable by future music teachers both in Estonia and Finland and what their potential could be developing cultural cohesion in society.